Protest Movements in Asylum and Deportation (IMISCOE Research Series,, 2018)
This open access book deals with contestations "from below" of legal policies and implementation practices in asylum and deportation. Consequently, it covers three types of mobilization: solidarity protests against the deportation of refused asylum seekers, refugee activism campaigning for residence rights and inclusion, and restrictive protests against the reception of asylum seekers. By applying both a longitudinal analysis of protest events and a series of in-depth case studies in three immigration countries, this edited volume provides comparative insights into these three types of movement in Austria, Germany, and Switzerland over a time span of twenty-five years. Embedded in concepts of political change, limited state sovereignty, and migration control, the findings shed light on actors, repertoires, and the effects of protest activities. The contributions illustrate how local contexts, national political settings, issue specifics, and social ties lead to distinctly different forms of protest emergence, dynamics, and strategies. Additionally, they give a profound understanding of the mechanisms and constellations that contribute to protest success, both in terms of preventing deportations of individuals as well as changing policies. In sum, this book constitutes a major contribution to empirically informed theoretical reflections on collective contestation in the fields of refugee studies and social protest movements.